Processos excludentes e produção do espaço urbano em cidades pequenas paulistas: os casos de Capão Bonito, Buri e Ribeirão Grande - Moreira Junior, Orlando (2009)
The present work aims to elaborate an acquaintance about the social and spatial inequalities still few studied in non-metropolitan urban realities, specifically in small towns. Therefore this dissertation attempts to weave some considerations about the production of urban spaces in São Paulo small towns, examining the practices and actions of the producers agents of the urban space, which contribute to an unequal and excluding social-spatial formation, making a reflection from a study case in Capão Bonito, Buri and Ribeirão Grande, in order to achieve an analysis that allows to understand how public and private spheres and the civil society contribute in different ways to the unequal production of urban spaces, seeking to identify, in different perspectives, how exclusion is manifested in these urban realities. Thus, we seek to contribute to a deeper theoretical understanding of excluding processes in small towns in São Paulo State. The concept of spatial deconstruction is used as an analytical instrument to interpret space production and this research was made feasible by a bibliographic gathering, fieldwork and collection, data analysis and systematization that allowed a spatial reading of exclusion to indicate in different perspectives, how the phenomenon manifests itself both in the intra-urban scale and in the intercity scale. For this purpose we seek to contextualize the small towns from the economical aspects linked to the urbanization process, through what is possible to verify the constitution of Brazilian urban network guided by the competition between cities. Then reflect if the small towns, in this context, are excluding territories and emphasize the importance of thinking about solutions, mainly in territorial management and integrated urban network, turning possible to minimize the socio-spatial inequalities that afflict small towns.